Pengetahuan, Sikap, dan Perilaku Pengguna Metode Kontrasepsi Jangka Panjang dan Pendek di Daerah Terpencil Indonesia - Hani Sri Fitriani; Pratiwi Wikaningtyas; Zulfan Zazuli (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
The use of long-acting contraceptive methods (LACMs) in Indonesia remains relatively low despite government efforts to increase their adoption to reduce maternal and child mortality. This study aims to examine differences in knowledge, attitudes, and practices (KAP) between LACM users and non-LACM users, as well as to identify factors influencing contraceptive method selection among women of reproductive age in a rural area of Indonesia. A cross-sectional design was employed involving 394 respondents selected through Cluster Random Sampling, all of whom completed validated and reliable questionnaires. Data were analyzed descriptively. The Mann–Whitney test was used to compare KAP between LACM and non-LACM users. Chi-square tests and logistic regression analysis were conducted to identify factors associated with contraceptive method selection. The results showed significant differences between the two groups. LACM users demonstrated higher levels of knowledge, more positive attitudes, and better contraceptive practices compared with non-LACM users. Factors associated with LACM use included high knowledge (OR = 2.415; p = 0.001), education above primary school level (OR = 7.03; p = 0.003), exposure to print media (OR = 28.331; p = 0.000), and obtaining contraceptives from community health centers (OR = 6.6; p = 0.009). In conclusion, short-acting contraceptive users exhibited lower knowledge, attitudes, and practices than LACM users. Therefore, individuals with low KAP levels should be prioritized in reproductive health education and promotion programs.